Pengembangan Website Speech To Video Bahasa Isyarat Indonesia (Bisindo) Berbasis Algoritma Long Shot Term Memory - Deleviar, Angky Fay; Intan Oktaviani; Hanifah Permatasari (Fakultas Teknik Universitas Hamzanwadi, 2025)
Indonesian Sign Language (BISINDO) is an essential communication tool for more than one million deaf people in Indonesia. This research aims to develop a Speech to BISINDO website based on the Long Short-Term Memory (LSTM) algorithm to overcome barriers in communication and learning processes for the deaf community. The research stages include data collection through questionnaires and literature studies to understand user needs, as well as system development using the Rational Unified Process (RUP) method. The system is designed to convert voice input into sign language videos and support the sign language learning process through interactive features. Testing was conducted to ensure that the system meets functional and non-functional needs. The results show that the Speech to BISINDO website is effective in translating speech into sign language videos with high accuracy, as well as supporting better communication and learning between deaf people and the general public. The system offers an innovative solution to improve access to information and learning process for people with hearing impairment.